The role of excellent service in enchasing the appeal of Tomok Tourism Village, Samosir Island, North Sumatera - Anbo Mahadu Simanjuntak (Borneo Novelty Publishing, 2024)
Purpose - The purpose of this study is to explore the role of excellent service in improving the tourist experience in Tomok Tourism Village, located on Samosir Island, North Sumatra. It aims to identify how service quality can enhance the attractiveness of the village for visitors. Methodology/Design/Approach - The study uses interviews, observations, and a literature review, focusing on both business operators and visitors to gather insights on the impact of service quality on tourism satisfaction. Finding - The study found that friendly, prompt, and professional service plays a significant role in enhancing tourist satisfaction and encouraging repeat visits. High-quality service directly influences tourists' overall experience and their likelihood of returning. Originality/Value - This research provides valuable recommendations for village managers to improve service standards, which could help attract more tourists to Tomok Village. It emphasizes the importance of excellent service in creating a positive and lasting impression on visitors.